Synthesis of Hydrogen Getter Zr1-xCox (x=0-1) Alloy Films by Magnetron Co-Sputtering - Dhonge, Baban P.; Singh, Akash; Panda, Arun K.; Srihari, Velaga; Thirumurugesan, R.; Parida, Pradyumna K.; Mythili, R.; Parameswaran, P. (Journal of Coating Science and Technology, 2020)
The Zr1-xCox(x=0, 0.25, 0.53, 0.63, 1) thin films were deposited on quartz substrate using magnetron co-sputtering of Zirconium and Cobalt targets in confocal geometry. A constant pulsed direct current (PDC) on Zirconium and radio frequency (RF) of various powers on Cobalt target were applied to vary the concentration of Co in the Zr1-xCox film. The film composition was quantified using EDX measurements. The hydrogen storage capacity of these films was studied using an in-house developed hydrogen adsorption setup, in which the electrical resistivity of the film was monitored as a function of hydrogen partial pressure and temperature. The films' surface morphology and crystal structure before and after hydrogenation were characterized using atomic force microscopy and grazing incidence X-ray diffraction techniques using synchrotron radiation, respectively. An increase in the particle size after hydrogenation was observed for all the films. An increase in resistivity was also observed due to the absorption of hydrogen in all the compositions. The near stoichiometric film Zr0.47Co0.53 showed the highest hydrogen absorption level at 200 oC at all partial pressures. However, a decrease in the response at temperatures higher than 200 oC was observed in the film containing a Co concentration. The mechanism for the increase in resistivity of the film on hydrogenation is explained